2016
DOI: 10.1088/2053-1583/3/3/035016
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity of MoS 2 polycrystalline nanomembranes

Abstract: We report a technique for transferring large areas of the CVD-grown, few-layer MoS 2 from the original substrate to another arbitrary substrate and onto holey substrates, in order to obtain freestanding structures. The method consists of a polymer-and residue-free, surface-tension-assisted wet transfer, in which we take advantage of the hydrophobic properties of the MoS 2. The methods yields better quality transferred layers, with fewer cracks and defects, and less contamination than the widely used PMMA-media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 46 publications
1
43
0
Order By: Relevance
“…Furthermore, the variation of the crystallinity between the two samples yields a variation in the grain boundary concentration. Just the presence of the grain boundaries was recently found to be responsible for reducing the in‐plane thermal conductivity of 5 nm thick polycrystalline MoS 2 film to 0.73 ± 0.25 W m −1 K −1 in the temperature range of 320–430 K . Even though grain boundary scattering of phonons has long been considered to be frequency independent by the gray model, Wang et al suggested that this is not the case and there is actually a phonon frequency dependence transmission coefficient through grain boundaries, that leads to a frequency‐dependent mean free path when phonons are scattered by grain boundaries.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the variation of the crystallinity between the two samples yields a variation in the grain boundary concentration. Just the presence of the grain boundaries was recently found to be responsible for reducing the in‐plane thermal conductivity of 5 nm thick polycrystalline MoS 2 film to 0.73 ± 0.25 W m −1 K −1 in the temperature range of 320–430 K . Even though grain boundary scattering of phonons has long been considered to be frequency independent by the gray model, Wang et al suggested that this is not the case and there is actually a phonon frequency dependence transmission coefficient through grain boundaries, that leads to a frequency‐dependent mean free path when phonons are scattered by grain boundaries.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, this information can help to guide the production methods and conditions necessary to achieve the material characteristics desired for a particular application. This issue is common to other 2D materials such as MoS 2 where, by combining two-laser Raman thermometry with finite element simulations, it has recently been shown that heat conduction can be effectively engineered by controlling the nanoscale grain size [143]. For sensing applications smaller grains may be desired, as point defects or GBs could improve the device performance, while for purely electronic applications larger grains would be ideal.…”
Section: Discussionmentioning
confidence: 99%
“…However, we consider that the κ of polycrystalline monolayers is smaller than that of single-crystalline monolayers because of the effects from domain/grain boundaries, and we would rather use the κ of large-area bulk samples. Very recently, the κ of polycrystalline MoS 2 films (thickness of >100 nm) have been measured, and its value is ranging from 0.5 to 1.5 W m −1 K −1 [46,47]. If we apply these results into our polycrystalline samples, the derived ZT is up to 0.1, suggesting that the measurement of κ in polycrystalline monolayers is an important future issue.…”
mentioning
confidence: 87%